Phylogenetic and morphological characterization of Komarekiella atlantica (Cyanobacteria, Nostocales) from southernmost subtropical Brazilian environments - Vanessa Maria Didoné; Luis Henrique Zanini Branco; Mariéllen Dornelles Martins; Vera Regina Werner (Brazilian Journal of Microbiology, 2026)

Selenium deficiency fastens intestinal barrier dysfunction and inflammation during high-fat/high-fructose-induced MASLD development in male mice - Nora Meinhardt; Anja R. Geisler; Laura Otto; Yvonne Hupfer; Betty Hebecker; Bill J. Perkowski; Markus Werner; Kristina Lossow; Marcus Ebert; Sandra Burghoff; Oliver Werz; Stefan Lorkowski; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Temperature, trophic state, and carrying capacity govern pelagic size spectra in the Atlantic Ocean - Ralf Schwamborn; Tim Dudeck; Claire Carré; Gabriel Bittencourt Farias; María Couret; Javier Díaz-Pérez; Mathilde Dugenne; Gabriela Guerra Araújo Abrantes de Figueiredo; Thierry Frédou; Flávia Lucena-Frédou; Xiomara F.G. Díaz; Dawit Yemane; et al. (Progress in Oceanography, 2026)

Habitat configuration and habitat quality shape butterfly diversity in tropical dry coastal forests of southern Kenya - Maria Mashirma Fungomeli; Werner Ulrich; Thomas Schmitt; Martin Wiemers; Mike Teucher; Jonas Eberle; Jan Christian Habel (Biodiversity and Conservation, 2026)

Cryosphere and lithology influence the hydrological gradients of high elevation Alpine catchments - Stefano Brighenti; Matteo Delpero; Francesca Bearzot; Giulia Bertolotti; Monica Tolotti; Maria Cristina Bruno; Andrea Fischer; Gerfried Winkler; Giulio Voto; Agnese Aguzzoni; Werner Tirler; Francesco Comiti (CATENA, 2026)

Eugenol as a natural antioxidant for porcine in vitro embryo production - Maria Valéria de Oliveira Santos; Karina Gutierrez; Werner Giehl Glanzner; Mariana Priotto de Macedo; Luke Currin; Alexsandra Fernandes Pereira; Vilceu Bordignon (Theriogenology, 2026)

Spatio-temporal variability of isotopic and chemical tracers in high-elevation water sources, Eastern European Alps - Matteo Delpero; Stefano Brighenti; Francesca Bearzot; Giulia Bertolotti; Monica Tolotti; Maria Cristina Bruno; Andrea Fischer; Gerfried Winkler; Werner Tirler; Leonardo Cerasino; Francesco Comiti (Journal of Hydrology, 2025)

Interdisciplinary investigations of a pristine alpine lake in Austria: The Lake Altaussee Monitoring Program (LAMP) - Dimitri D. Deheyn; Philipp Haeuselmann; Thomas Burschil; Stefano Fabbri; Markus Fiebig; Wolfgang Gasperl; Michael Grabner; Jean Nicolas Haas; Andreas Holzinger; Helmut Kalss; Werner Kofler; Cassandra C. Kremer; et al. (Total Environment Advances, 2025)

Global landscape of space weather observations, research and operations - Mamoru Ishii; Joaquim E.R. Costa; Maria Kuznetsova; Mario M. Bisi; Amalia Meza; Astrid M. Veronig; Clezio Marcos Denardini; Christina Plainaki; Sergio Dasso; Manuela Temmer; María Graciela Molina; Jens Berdermann; et al. (Advances in Space Research, 2025)

Tree Diversity Increases Forest Temperature Buffering via Enhancing Canopy Density and Structural Diversity - Florian Schnabel; Rémy Beugnon; Bo Yang; Ronny Richter; Nico Eisenhauer; Yuanyuan Huang; Xiaojuan Liu; Christian Wirth; Simone Cesarz; Andreas Fichtner; Maria D. Perles‐Garcia; Georg J. A. Hähn; et al. (Ecology Letters, 2025)
Global warming is increasing the frequency and intensity of climate extremes. Forests may buffer climate extremes by creating their own attenuated microclimate below their canopy, which maintains forest functioning and biodiversity. However, the effect of tree diversity on temperature buffering in forests is largely unexplored. Here, we show that tree species richness increases forest temperature buffering across temporal scales over six years in a large‐scale tree diversity experiment covering a species richness gradient of 1 to 24 tree species. We found that species richness strengthened the cooling of hot and the insulation against cold daily and monthly air temperatures and temperature extremes. This buffering effect of tree species richness was mediated by enhanced canopy density and structural diversity in species‐rich stands. Safeguarding and planting diverse forests may thus mitigate negative effects of global warming and climate extremes on below‐canopy ecosystem functions and communities.

Biochar Outperforms Biochar-Compost Mix in Stimulating Ecophysiological Responses and Enhancing Soil Fertility under Drought Conditions - Zainul Abideen; Hans Werner Koyro; Maria Hasnain; Muhammad Iftikhar Hussain; Ali El-Keblawy; Mohamed A. El-Sheikh; Mirza Hasanuzzaman (Journal of Soil Science and Plant Nutrition, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Ecological “Windows of opportunity” influence biofilm prokaryotic diversity differently in glacial and non-glacial Alpine streams - Monica Tolotti; Stefano Brighenti; Maria Cristina Bruno; Leonardo Cerasino; Massimo Pindo; Werner Tirler; Davide Albanese (Science of The Total Environment, 2024)

Shades and shifts in flexitarian and meat-oriented consumer profiles in a German panel study - Anna-Maria Strässner; Werner Wirth (Appetite, 2024)

Landscape of global urban environmental resistome and its association with local socioeconomic and medical status - Jun Wu; Yige Hu; Michael H. Perlin; David Danko; Jun Lu; Manuela Oliveira; Johannes Werner; Maria M. Zambrano; Maria A. Sierra; Olayinka O. Osuolale; Paweł Łabaj; Nicolás Rascovan; et al. (Science China Life Sciences, 2024)

Aspergillosis in Critically Ill Patients with and Without COVID-19 in a Tertiary Hospital in Southern Brazil - Mariana Rodrigues Trápaga; Vanice Rodrigues Poester; Rossana Patrícia Basso; Bianca dos Santos Blan; Lívia Silveira Munhoz; Alessandro C. Pasqualotto; Talita da Fontoura Werner; Maria Letícia Figurelli; David A. Stevens; Andrea von Groll; Melissa Orzechowski Xavier (Mycopathologia, 2024)

Arabinan-rich pectic polysaccharide fraction from Malpighia emarginata fruits alleviates inflammatory pain in mice - Jorge Luiz Dallazen; Paula Giovanna Ciapparini; Daniele Maria-Ferreira; Bruna Barbosa da Luz; Rafael Roberto Klosterhoff; Letícia Polli Glugoski Felipe; Bruno José Gonçalves Silva; Lucimara M.C. Cordeiro; Maria Fernanda de Paula Werner (Food Research International, 2024)

Prebiotics and the Risk of Upper Digestive Tract and Stomach Cancers: The PrebiotiCa Study - Federica Turati; Federica Concina; Paola Bertuccio; Federica Fiori; Maria Parpinel; Werner Garavello; Anna Crispo; Massimo Libra; Eva Negri; Diego Serraino; Carlo La Vecchia (Journal of the Academy of Nutrition and Dietetics, 2023)

RETRACTED: Future warming stimulates growth and photosynthesis in an Arctic microalga more strongly than changes in light intensity or pCO 2 - Sebastian D. Rokitta; Christian H. Grossmann; Elisa Werner; Jannika Moye; Giulia Castellani; Eva‐Maria Nöthig; Björn Rost (Limnology and Oceanography, 2023)
We assessed the responses of solitary cells of Arctic Phaeocystis pouchetii grown under a matrix of temperature (2°C vs. 6°C), light intensity (55 vs. 160 μ mol photons m −2 s −1 ) and pCO 2 (400 vs. 1000 μ atm CO 2 , i.e., 40.5 vs. 101.3 Pa). Next to acclimation parameters (growth rates, particulate and dissolved organic C and N, Chlorophyll a content), we measured physiological processes in vivo (electron transport rates and net photosynthesis) using fast‐repetition rate fluorometry and membrane‐inlet mass spectrometry. Within the applied driver ranges, elevated temperature had the most pronounced impacts, significantly increasing growth, elemental quotas and photosynthetic performance. Light stimulations manifested more prominently under 6°C, underlining temperature's role as a “master‐variable”. pCO 2 was the least effective driver, exerting mostly insignificant effects. The obtained data were used for a simplistic upscaling simulation to investigate potential changes in P. pouchetii 's bloom dynamics in the Fram Strait with increasing temperatures over the 21 st century. Although solitary cells might not be fully representative of colonial cells commonly observed in the field, our results suggest that global warming accelerates bloom dynamics, with earlier onsets of blooms and higher peak biomasses. Such a temperature‐induced acceleration in the phenology of Phaeocystis and likely other Arctic phytoplankton might cause temporal mismatches, e.g., with the development of grazers, and therefore substantially affect the biogeochemistry and ecology of the Arctic.

CPW partially attenuates DSS-induced ulcerative colitis in mice - Natalia Mulinari Turin de Oliveira; Vanessa S. Schneider; Laryssa Regis Bueno; Lara Luisa Valerio de Mello Braga; Karien Sauruk da Silva; Liziane Cristine Malaquias da Silva; Maria Luiza Souza; Bruna Barbosa da Luz; Cleiane Dias Lima; Ruan Sousa Bastos; Maria Fernanda de Paula Werner; Elizabeth Soares Fernandes; et al. (Food Research International, 2023)

Water-soluble polysaccharides from Piper regnellii (Pariparoba) leaves: Structural characterization and antinociceptive and anti-inflammatory activities - Giuliana Cozzella Campo-Grande; Bruna Barbosa da Luz; Daniele Maria-Ferreira; Maria Fernanda de Paula Werner; Thales Ricardo Cipriani (Carbohydrate Polymers, 2023)

Bacterial genome sequencing tracks the housefly‐associated dispersal of fluoroquinolone‐ and cephalosporin‐resistant Escherichia coli from a pig farm - Wiebke Behrens; Baban Kolte; Vera Junker; Martinique Frentrup; Claudia Dolsdorf; Maria Börger; Megarsa Jaleta; Tina Kabelitz; Thomas Amon; Doreen Werner; Ulrich Nübel (Environmental Microbiology, 2023)
The regular use of antimicrobials in livestock production selects for antimicrobial resistance. The potential impact of this practice on human health needs to be studied in more detail, including the role of the environment for the persistence and transmission of antimicrobial‐resistant bacteria. During an investigation of a pig farm and its surroundings in Brandenburg, Germany, we detected abundant cephalosporin‐ and fluoroquinolone‐resistant Escherichia coli in pig faeces, sedimented dust, and house flies ( Musca domestica ). Genome sequencing of E. coli isolates revealed large phylogenetic diversity and plasmid‐borne extended‐spectrum beta lactamase (ESBL) genes CTX‐M‐1 in multiple strains. [Correction added on 28 February 2023, after first online publication: In the preceding sentence, ‘and TEM‐1’ was previously included but has been deleted in this version.] Close genomic relationships indicated frequent transmission of antimicrobial‐resistant E. coli between pigs from different herds and across buildings of the farm and suggested dust and flies as vectors for dissemination of faecal pathogens. Strikingly, we repeatedly recovered E. coli from flies collected up to 2 km away from the source, whose genome sequences were identical or closely related to those from pig faeces isolates, indicating the fly‐associated transport of diverse ESBL‐producing E. coli from the pig farm into urban habitation areas. The observed proximity of contaminated flies to human households poses a risk of transmission of antimicrobial‐resistant enteric pathogens from livestock to man.

Investigation of the chemical structure and analgesic and anti-inflammatory properties of polysaccharides that constitute the dietary fibers of soursop (Annona muricata) fruit - Carolina Lopes Leivas; Thaisa Moro Cantu-Jungles; Bruna Barbosa da Luz; Maria Fernanda de Paula Werner; Marcello Iacomini; Lucimara M. C. Cordeiro (Food Research International, 2023)

In vivo ligamentogenesis in embroidered poly(lactic-co-ε-caprolactone) / polylactic acid scaffolds functionalized by fluorination and hexamethylene diisocyanate cross-linked collagen foams - Maria Kokozidou; Clemens Gögele; Felix Pirrung; Niels Hammer; Christian Werner; Benjamin Kohl; Judith Hahn; Annette Breier; Michaela Schröpfer; Michael Meyer; Gundula Schulze-Tanzil (Histochemistry and Cell Biology, 2023)
Although autografts represent the gold standard for anterior cruciate ligament (ACL) reconstruction, tissue-engineered ACLs provide a prospect to minimize donor site morbidity and limited graft availability. This study characterizes the ligamentogenesis in embroidered poly( L -lactide- co -ε-caprolactone) (P(LA-CL)) / polylactic acid (PLA) constructs using a dynamic nude mice xenograft model. (P(LA-CL))/PLA scaffolds remained either untreated (co) or were functionalized by gas fluorination (F), collagen foam cross-linked with hexamethylene diisocyanate (HMDI) (coll), or F combined with the foam (F + coll). Cell-free constructs or those seeded for 1 week with lapine ACL ligamentocytes were implanted into nude mice for 12 weeks. Following explantation, cell vitality and content, histo(patho)logy of scaffolds (including organs: liver, kidney, spleen), sulphated glycosaminoglycan (sGAG) contents and biomechanical properties were assessed. Scaffolds did not affect mice weight development and organs, indicating no organ toxicity. Moreover, scaffolds maintained their size and shape and reflected a high cell viability prior to and following implantation. Coll or F + coll scaffolds seeded with cells yielded superior macroscopic properties compared to the controls. Mild signs of inflammation (foreign-body giant cells and hyperemia) were limited to scaffolds without collagen. Microscopical score values and sGAG content did not differ significantly. Although remaining stable after explantation, elastic modulus, maximum force, tensile strength and strain at F max were significantly lower in explanted scaffolds compared to those before implantation, with no significant differences between scaffold subtypes, except for a higher maximum force in F + coll compared with F samples (in vivo). Scaffold functionalization with fluorinated collagen foam provides a promising approach for ACL tissue engineering. Graphical abstract a Lapine anterior cruciate ligament (LACL): red arrow, posterior cruciate ligament: yellow arrow. Medial anterior meniscotibial ligament: black arrow. b Explant culture to isolate LACL fibroblasts. c Scaffold variants: co: controls; F: functionalization by gas-phase fluorination; coll: collagen foam cross-linked with hexamethylene diisocyanate (HMDI). c1-2 Embroidery pattern of the scaffolds. d Scaffolds were seeded with LACL fibroblasts using a dynamical culturing approach as depicted. e Scaffolds were implanted subnuchally into nude mice, fixed at the nuchal ligament and sacrospinal muscle tendons. f Two weeks after implantation. g Summary of analyses performed. Scale bars 1 cm ( b , d ), 0.5 cm ( c ). (sketches drawn by G.S.-T. using Krita 4.1.7 [Krita foundation, The Netherlands]).

Optimization of gonadotropin stimulation protocols for in vitro embryo production in prepubertal Mediterranean water buffalo - Luke Currin; Hernan Baldassarre; Mariana Priotto de Macedo; Werner Giehl Glanzner; Karina Gutierrez; Katerina Lazaris; Zigomar da Silva; Vanessa Guay; Maria Elena Carrillo Herrera; Caitlin Brown; Erin Joron; Ron Herron; et al. (Theriogenology, 2023)

Involvement of a neutrophil-mast cell axis in the effects of Piper malacophyllum (C. PESL) C. DC extract and its isolated compounds in a mouse model of dysmenorrhoea - Nara Lins Meira Quintão; Jaqueline Pavesi Reis; Larissa Benvenutti; Roberta Nunes; Fernanda Capitanio Goldoni; Manuela Somensi Cozer; Priscila de Souza; Rita de Cássia Melo Vilhena de Andrade F; Jessica Melato; Carlos Rafael Vaz; Juliana Cristina Pereira Whitaker; Flavia Werner Jesuíno; et al. (Inflammopharmacology, 2022)

Thermal requirements and estimates of the annual number of generations of Heliothrips haemorrhoidalis in strawberry-producing regions of Brazil - Mireli Trombin de Souza; Michele Trombin de Souza; Simone Silmara Werner; Maria Aparecida Cassilha Zawadneak (Phytoparasitica, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The aquaponic principle—It is all about coupling - Gösta F. M. Baganz; Ranka Junge; Maria C. Portella; Simon Goddek; Karel J. Keesman; Daniela Baganz; Georg Staaks; Christopher Shaw; Frank Lohrberg; Werner Kloas (Reviews in Aquaculture, 2022)
The aquaponic principle is the coupling of animal aquaculture (e.g. fish) with plant production (e.g. vegetables) for saving resources. At present, various definitions of aquaponics exist, some bearing the risk of misinterpretation by dismissing the original meaning or being contradictory. In addition, there is no standard terminology for the aspects of coupling between the aquaponic subsystems. In this study, we addressed both issues. (1) We developed new or revised definitions that are summarised by: Aquaponic farming comprises aquaponics (which couples tank‐based animal aquaculture with hydroponics) and trans‐aquaponics, which extends aquaponics to tankless aquaculture as well as non‐hydroponics plant cultivation methods. Within our conceptual system, the term aquaponics corresponds to the definitions of FAO and EU. (2) A system analysis approach was utilised to explore different aquaponic setups aiming to better describe the way aquaponic subsystems are connected. We introduced the new terms ‘coupling type’ and ‘coupling degree’, where the former qualitatively characterises the water‐mediated connections of aquaponic subsystems. A system with on‐demand nutrient water supply for the independent operating plant cultivation is an ‘on‐demand coupled system’ and we propose to deprecate the counterintuitive term ‘decoupled system’ for this coupling type. The coupling degree comprises a set of parameters to quantitatively determine the coupling's efficiency of internal streams, for example, water and nutrients. This new framework forms a basis for improved communication, provides a uniform metric for comparing aquaponic facilities, and offers criteria for facility optimisation. In future system descriptions, it will simplify evaluation of the coupling's contribution to sustainability of aquaponics.

How to report the antinuclear antibodies (anti-cell antibodies) test on HEp-2 cells: guidelines from the ICAP initiative - Carlos Alberto von Mühlen; Ignacio Garcia-De La Torre; Maria Infantino; Jan Damoiseaux; Luis E. C. Andrade; Orlando Gabriel Carballo; Karsten Conrad; Paulo Luiz Carvalho Francescantonio; Marvin J. Fritzler; Manfred Herold; Werner Klotz; Wilson de Melo Cruvinel; et al. (Immunologic Research, 2021)

Trait-based responses to cessation of nutrient enrichment in a tundra plant community - Chhaya M. Werner; Maria Tuomi; Anu Eskelinen (Oecologia, 2021)
Plant communities worldwide show varied responses to nutrient enrichment—including shifts in species identity, decreased diversity, and changes in functional trait composition—but the factors determining community recovery after the cessation of nutrient addition remain uncertain. We manipulated nutrient levels in a tundra community for 6 years of nutrient addition followed by 8 years of recovery. We examined how community recovery was mediated by traits related to plant resource-use strategy and plant ability to modify their environment. Overall, we observed persistent effects of fertilization on plant communities. We found that plants with fast-growing traits, including higher specific leaf area, taller stature and lower foliar C:N, were more likely to show a persistent increase in fertilized plots than control plots, maintaining significantly higher cover in fertilized plots 8 years after cessation of fertilization. Additionally, although graminoids responded most strongly to the initial fertilization treatment, forb species were more vulnerable to fertilization effects in the long-term, showing persistent decline and no recovery in 8 years. Finally, these persistent fertilization effects were accompanied by modified environmental conditions, including persistent increases in litter depth and soil phosphorous and lower soil C:N. Our results demonstrate the potential for lasting effects of nutrient enrichment in nutrient-limited systems and identify species traits related to rapid growth and nutrient-use efficiency as the main predictors of the persistence of nutrient enrichment effects. These findings highlight the usefulness of trait-based approach for understanding the persistent feedbacks of nutrient enrichment, plant dynamics, and niche construction via litter and nutrient build-up.

Fertilized graminoids intensify negative drought effects on grassland productivity - Kevin Van Sundert; Mohammed A. S. Arfin Khan; Siddharth Bharath; Yvonne M. Buckley; Maria C. Caldeira; Ian Donohue; Maren Dubbert; Anne Ebeling; Nico Eisenhauer; Anu Eskelinen; Alain Finn; Tobias Gebauer; et al. (Global Change Biology, 2021)
Droughts can strongly affect grassland productivity and biodiversity, but responses differ widely. Nutrient availability may be a critical factor explaining this variation, but is often ignored in analyses of drought responses. Here, we used a standardized nutrient addition experiment covering 10 European grasslands to test if full‐factorial nitrogen, phosphorus, and potassium addition affected plant community responses to inter‐annual variation in drought stress and to the extreme summer drought of 2018 in Europe. We found that nutrient addition amplified detrimental drought effects on community aboveground biomass production. Drought effects also differed between functional groups, with a negative effect on graminoid but not forb biomass production. Our results imply that eutrophication in grasslands, which promotes dominance of drought‐sensitive graminoids over forbs, amplifies detrimental drought effects. In terms of climate change adaptation, agricultural management would benefit from taking into account differential drought impacts on fertilized versus unfertilized grasslands, which differ in ecosystem services they provide to society.

Toward a Comprehensive and Integrated Strategy of the European Marine Research Infrastructures for Ocean Observations - Juan Jose Dañobeitia; Sylvie Pouliquen; Truls Johannessen; Alberto Basset; Mathilde Cannat; Benjamin Gerrit Pfeil; Maria Incoronata Fredella; Paola Materia; Claire Gourcuff; Giuseppe Magnifico; Eric Delory; Joaquin del Rio Fernandez; et al. (Frontiers in Marine Science, 2020)

Pharmacological potential of alkylamides from Acmella oleracea flowers and synthetic isobutylalkyl amide to treat inflammatory pain - Jorge Luiz Dallazen; Daniele Maria-Ferreira; Bruna Barbosa da Luz; Adamara Machado Nascimento; Thales Ricardo Cipriani; Lauro Mera de Souza; Letícia Polli Glugoski Felipe; Bruno José Gonçalves Silva; Romina Nassini; Maria Fernanda de Paula Werner (Inflammopharmacology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Stichprobenplanung in der Lebensmittelüberwachung: Reduktion des notwendigen Stichprobenumfangs durch Pooling - Inga Ruddat; Friedemann Adler; Maria Hartmann; Anna Wendt; Nicole Werner; Katrin Blume; Oliver Lindtner; Anja Lüth; Thilo Nölke; Matthias Greiner; Amely Campe (Journal of Consumer Protection and Food Safety, 2019)

Forest decision support systems for the analysis of ecosystem services provisioning at the landscape scale under global climate and market change scenarios - Eva-Maria Nordström; Maarten Nieuwenhuis; Emin Zeki Başkent; Peter Biber; Kevin Black; Jose G. Borges; Miguel N. Bugalho; Giulia Corradini; Edwin Corrigan; Ljusk Ola Eriksson; Adam Felton; Nicklas Forsell; et al. (European Journal of Forest Research, 2019)

Effect of Synadenium grantii and its isolated compound on dysmenorrhea behavior model in mice - Flávia Werner da Rocha Jesuíno; Jaqueline Pavesi Reis; Juliana Cristina Pereira Whitaker; Adriana Campos; Maria Verônica Dávila Pastor; Valdir Cechinel Filho; Nara Lins Meira Quintão (Inflammopharmacology, 2019)

Effect of simvastatin on sensorial, motor, and morphological parameters in sciatic nerve crush induced-neuropathic pain in rats - Claudia Rita Corso; Daniel Fernandes Martins; Stephanie Carvalho Borges; Olair Carlos Beltrame; José Ederaldo Queiroz Telles; Nilza Cristina Buttow; Maria Fernanda de Paula Werner (Inflammopharmacology, 2018)

Acid-gastric antisecretory effect of the ethanolic extract from Arctium lappa L. root: role of H+, K+-ATPase, Ca2+ influx and the cholinergic pathway - Luisa Mota da Silva; Ligia de Moura Burci; Sandra Crestani; Priscila de Souza; Rita de Cássia Melo Vilhena de Andr da Silva; Nessana Dartora; Lauro Mera de Souza; Thales Ricardo Cipriani; José Eduardo da Silva-Santos; Eunice André; Maria Fernanda de Paula Werner (Inflammopharmacology, 2018)

The formation of estrogen-like tamoxifen metabolites and their influence on enzyme activity and gene expression of ADME genes - Janina Johänning; Patrick Kröner; Maria Thomas; Ulrich M. Zanger; Astrid Nörenberg; Michel Eichelbaum; Matthias Schwab; Hiltrud Brauch; Werner Schroth; Thomas E. Mürdter (Archives of Toxicology, 2018)

Prioritization of substances for national ambient monitoring of sediment in Switzerland - Maria del Carmen Casado-Martinez; Michel Wildi; Benoit J.D. Ferrari; Inge Werner (Environmental Science and Pollution Research, 2018)

Was endothermy in amniotes induced by an early stop in growth during ontogeny? - Jan Werner; Eva Maria Griebeler (The Science of Nature, 2017)

Hydroethanolic extract of Baccharis trimera promotes gastroprotection and healing of acute and chronic gastric ulcers induced by ethanol and acetic acid - Francislaine Aparecida dos Reis Lívero; Luisa Mota da Silva; Daniele Maria Ferreira; Larissa Favaretto Galuppo; Debora Gasparin Borato; Thiago Bruno Lima Prando; Emerson Luiz Botelho Lourenço; Regiane Lauriano Batista Strapasson; Maria Élida Alves Stefanello; Maria Fernanda de Paula Werner; Alexandra Acco (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Quality assurance of diatom counts in Europe: towards harmonized datasets - Maria Kahlert; Éva Ács; Salome F. P. Almeida; Saúl Blanco; Mirko Dreßler; Luc Ector; Satu Maaria Karjalainen; Antonia Liess; Adrienne Mertens; Jako van der Wal; Sirje Vilbaste; Petra Werner (Hydrobiologia, 2016)

Systemic symptoms predict presence or development of severe sepsis and septic shock - Jon Edman-Wallér; Lars Ljungström; Gunnar Jacobsson; Rune Andersson; Maria Werner (Infectious Diseases, 2016)

Healing mechanisms of the hydroalcoholic extract and ethyl acetate fraction of green tea (Camellia sinensis (L.) Kuntze) on chronic gastric ulcers - Débora Gasparin Borato; Camila Toledo Scoparo; Daniele Maria-Ferreira; Luísa Mota da Silva; Lauro Mera de Souza; Marcello Iacomini; Maria Fernanda de Paula Werner; Cristiane Hatsuko Baggio (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Effect of diets enriched with rutin on blood parameters, oxidative biomarkers and pituitary hormone expression in silver catfish (Rhamdia quelen) - Tanise S. Pês; Etiane M. H. Saccol; Giovana M. Ourique; Érika P. Londero; Luciane T. Gressler; Isabela A. Finamor; Daniel A. Rotili; Jaqueline I. Golombieski; Werner G. Glanzner; Susana F. Llesuy; Paulo B. D. Gonçalves; João Radünz Neto; et al. (Fish Physiology and Biochemistry, 2016)

δ 2 H, δ 13 C and δ 18 O from whole wood, α -cellulose and lignin methoxyl groups in Pinus sylvestris : a multi-parameter approach - Maria Mischel; Jan Esper; Frank Keppler; Markus Greule; Willy Werner (Isotopes in Environmental and Health Studies, 2015)

Insulin-like Growth Factor 1 Differentially Affects Lithium Sensitivity of Lymphoblastoid Cell Lines from Lithium Responder and Non-responder Bipolar Disorder Patients - Elena Milanesi; Adva Hadar; Elisabetta Maffioletti; Haim Werner; Noam Shomron; Massimo Gennarelli; Thomas G. Schulze; Marta Costa; Maria Del Zompo; Alessio Squassina; David Gurwitz (Journal of Molecular Neuroscience, 2015)

Tree-rings and people – different views on the 1540 Megadrought. Reply to Büntgen et al. 2015 - Christian Pfister; Oliver Wetter; Rudolf Brázdil; Petr Dobrovolný; Rüdiger Glaser; Jürg Luterbacher; Sonia I. Seneviratne; Eduardo Zorita; Maria-Joao Alcoforado; Mariano Barriendos; Ursula Bieber; Karl H. Burmeister; et al. (Climatic Change, 2015)

Grassland management intensification weakens the associations among the diversities of multiple plant and animal taxa - Pete Manning; Martin M. Gossner; Oliver Bossdorf; Eric Allan; Yuan-Ye Zhang; Daniel Prati; Nico Blüthgen; Steffen Boch; Stefan Böhm; Carmen Börschig; Norbert Hölzel; Kirsten Jung; et al. (Ecology, 2015)
Land‐use intensification is a key driver of biodiversity change. However, little is known about how it alters relationships between the diversities of different taxonomic groups, which are often correlated due to shared environmental drivers and trophic interactions. Using data from 150 grassland sites, we examined how land‐use intensification (increased fertilization, higher livestock densities, and increased mowing frequency) altered correlations between the species richness of 15 plant, invertebrate, and vertebrate taxa. We found that 54% of pairwise correlations between taxonomic groups were significant and positive among all grasslands, while only one was negative. Higher land‐use intensity substantially weakened these correlations (35% decrease in r and 43% fewer significant pairwise correlations at high intensity), a pattern which may emerge as a result of biodiversity declines and the breakdown of specialized relationships in these conditions. Nevertheless, some groups (Coleoptera, Heteroptera, Hymenoptera and Orthoptera) were consistently correlated with multidiversity, an aggregate measure of total biodiversity comprised of the standardized diversities of multiple taxa, at both high and low land‐use intensity. The form of intensification was also important; increased fertilization and mowing frequency typically weakened plant–plant and plant–primary consumer correlations, whereas grazing intensification did not. This may reflect decreased habitat heterogeneity under mowing and fertilization and increased habitat heterogeneity under grazing. While these results urge caution in using certain taxonomic groups to monitor impacts of agricultural management on biodiversity, they also suggest that the diversities of some groups are reasonably robust indicators of total biodiversity across a range of conditions.

Short-Term Cuprizone Feeding Verifies N-Acetylaspartate Quantification as a Marker of Neurodegeneration - Barbara Maria Krauspe; Wolfgang Dreher; Cordian Beyer; Werner Baumgartner; Bernd Denecke; Katharina Janssen; Claus-Dieter Langhans; Tim Clarner; Markus Kipp (Journal of Molecular Neuroscience, 2015)

Climate and soil attributes determine plant species turnover in global drylands - Werner Ulrich; Santiago Soliveres; Fernando T. Maestre; Nicholas J. Gotelli; José L. Quero; Manuel Delgado‐Baquerizo; Matthew A. Bowker; David J. Eldridge; Victoria Ochoa; Beatriz Gozalo; Enrique Valencia; Miguel Berdugo; et al. (Journal of Biogeography, 2014)
Aim Geographical, climatic and soil factors are major drivers of plant beta diversity, but their importance for dryland plant communities is poorly known. The aim of this study was to: (1) characterize patterns of beta diversity in global drylands; (2) detect common environmental drivers of beta diversity; and (3) test for thresholds in environmental conditions driving potential shifts in plant species composition. Location Global. Methods Beta diversity was quantified in 224 dryland plant communities from 22 geographical regions on all continents except Antarctica using four complementary measures: the percentage of singletons (species occurring at only one site); Whittaker's beta diversity, β(W); a directional beta diversity metric based on the correlation in species occurrences among spatially contiguous sites, β( R 2 ); and a multivariate abundance‐based metric, β( MV ). We used linear modelling to quantify the relationships between these metrics of beta diversity and geographical, climatic and soil variables. Results Soil fertility and variability in temperature and rainfall, and to a lesser extent latitude, were the most important environmental predictors of beta diversity. Metrics related to species identity [percentage of singletons and β(W)] were most sensitive to soil fertility, whereas those metrics related to environmental gradients and abundance [(β( R 2 ) and β( MV )] were more associated with climate variability. Interactions among soil variables, climatic factors and plant cover were not important determinants of beta diversity. Sites receiving less than 178 mm of annual rainfall differed sharply in species composition from more mesic sites (> 200 mm). Main conclusions Soil fertility and variability in temperature and rainfall are the most important environmental predictors of variation in plant beta diversity in global drylands. Our results suggest that those sites annually receiving c . 178 mm of rainfall will be especially sensitive to future climate changes. These findings may help to define appropriate conservation strategies for mitigating effects of climate change on dryland vegetation.

Species richness, diversity and density of understory vegetation along disturbance gradients in the Himalayan conifer forest - Kesang Wangchuk; András Darabant; Prem Bahadur Rai; Maria Wurzinger; Werner Zollitsch; Georg Gratzer (Journal of Mountain Science, 2014)

Erratum to: The year-long unprecedented European heat and drought of 1540 – a worst case - Oliver Wetter; Christian Pfister; Johannes P. Werner; Eduardo Zorita; Sebastian Wagner; Sonia I. Seneviratne; Jürgen Herget; Uwe Grünewald; Jürg Luterbacher; Maria-Joao Alcoforado; Mariano Barriendos; Ursula Bieber; et al. (Climatic Change, 2014)

The year-long unprecedented European heat and drought of 1540 – a worst case - Oliver Wetter; Christian Pfister; Johannes P. Werner; Eduardo Zorita; Sebastian Wagner; Sonia I. Seneviratne; Jürgen Herget; Uwe Grünewald; Jürg Luterbacher; Maria-Joao Alcoforado; Mariano Barriendos; Ursula Bieber; et al. (Climatic Change, 2014)

Genetic variation of horse chestnut and red horse chestnut and trees susceptibility to Erysiphe flexuosa and Cameraria ohridella - Lidia Irzykowska; Maria Werner; Jan Bocianowski; Zbigniew Karolewski; Dorota Frużyńska-Jóźwiak (Biologia, 2013)

Paleomagnetism and magnetic mineralogy of metabasites and granulites from Orlica-Śnieżnik Dome (Central Sudetes) - Magdalena Kądziałko-Hofmokl; Jacek Szczepański; Tomasz Werner; Maria Jeleńska; Krzysztof Nejbert (Acta Geophysica, 2013)

Reproductive investment in moa: a K-selected life-history strategy? - Jan Werner; Eva Maria Griebeler (Evolutionary Ecology, 2012)

Pathogens as potential hitchhikers on intercontinental dust - Ilka Toepfer; Jocelyne Favet; Anette Schulte; Maria Schmölling; Werner Butte; Eric W. Triplett; William J. Broughton; Anna A. Gorbushina (Aerobiologia, 2012)

Microbial eukaryote life in the new hypersaline deep-sea basin Thetis - Alexandra Stock; Hans-Werner Breiner; Maria Pachiadaki; Virginia Edgcomb; Sabine Filker; Violetta La Cono; Michail M. Yakimov; Thorsten Stoeck (Extremophiles, 2012)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Cadmium, copper, lead, and zinc in Mugil cephalus from seven coastal lagoons of NW Mexico - Martin G. Frías-Espericueta; J. Isidro Osuna-López; Martha A. Jiménez-Vega; Daniel Castillo-Bueso; Maria D. Muy-Rangel; Werner Rubio-Carrasco; Gabriel López-López; Gildardo Izaguirre-Fierro; Domenico Voltolina (Environmental Monitoring and Assessment, 2011)

Socioeconomic characteristics of urban and peri-urban dairy production systems in the North western Ethiopian highlands - Yitaye Alemayehu Ayenew; Maria Wurzinger; Azage Tegegne; Werner Zollitsch (Tropical Animal Health and Production, 2011)

Evaluation of non-chemical seed treatment methods for the control of Alternaria dauci and A. radicina on carrot seeds - Eckhard Koch; Annegret Schmitt; Dietrich Stephan; Carola Kromphardt; Marga Jahn; Hermann-Josef Krauthausen; Gustaf Forsberg; Sigrid Werner; Tahsein Amein; Sandra A. I. Wright; Federico Tinivella; Maria L. Gullino; et al. (European Journal of Plant Pathology, 2010)

Performance and limitation of two dairy production systems in the North western Ethiopian highlands - Yitaye Alemayehu Ayenew; Maria Wurzinger; Azage Tegegne; Werner Zollitsch (Tropical Animal Health and Production, 2009)

Biotic, Abiotic, and Management Controls on the Net Ecosystem CO2 Exchange of European Mountain Grassland Ecosystems - Georg Wohlfahrt; Margaret Anderson-Dunn; Michael Bahn; Manuela Balzarolo; Frank Berninger; Claire Campbell; Arnaud Carrara; Alessandro Cescatti; Torben Christensen; Sabina Dore; Werner Eugster; Thomas Friborg; et al. (Ecosystems, 2008)

Data, not only in aerobiology: how normal is the normal distribution? - Eckhard Limpert; James Burke; Carmen Galan; Maria del Mar Trigo; Jonathan S. West; Werner A. Stahel (Aerobiologia, 2008)

Sialic acid metabolism is involved in the regulation of gene expression during neuronal differentiation of PC12 cells - Maria Kontou; Christian Bauer; Werner Reutter; Rüdiger Horstkorte (Glycoconjugate Journal, 2008)

Primed-site Probing of Papain-like Cysteine Proteases - José Maria Pfizer; Irmgard Assfalg-Machleidt; Werner Machleidt; Luis Moroder; Norbert Schaschke (International Journal of Peptide Research and Therapeutics, 2007)

Introductory perspective on the COREF Project - Yasufumi Iryu; Hiroki Matsuda; Hideaki Machiyama; Werner E. Piller; Terrence M. Quinn; Maria Mutti (Island Arc, 2006)
Coral reefs are tropic to subtropic, coastal ecosystems comprising very diverse organisms. Late Quaternary reef deposits are fossil archives of environmental, tectonic and eustatic variations that can be used to reconstruct the paleoclimatic and paleoceanographic history of the tropic surface oceans. Reefs located at the latitudinal limits of coral‐reef ecosystems (i.e. those at coral‐reef fronts) are particularly sensitive to environmental changes – especially those associated with glacial–interglacial changes in climate and sealevel. We propose a land and ocean scientific drilling campaign in the Ryukyu Islands (the Ryukyus) in the northwestern Pacific Ocean to investigate the dynamic response of the corals and coral‐reef ecosystems in this region to Late Quaternary climate and sealevel change. Such a drilling campaign, which we call the COREF (coral‐reef front) Project, will allow the following three major questions to be evaluated: (i) What are the nature, magnitude and driving mechanisms of coral‐reef front migration in the Ryukyus? (ii) What is the ecosystem response of coral reefs in the Ryukyus to Quaternary climate changes? (iii) What is the role of coral reefs in the global carbon cycle? Subsidiary objectives include (i) the timing of coral‐reef initiation in the Ryukyus and its causes; (ii) the position of the Kuroshio current during glacial periods and its effects on coral‐reef formation; and (iii) early carbonate diagenetic responses as a function of compounded variations in climate, eustacy and depositional mineralogies (subtropic aragonitic to warm‐temperate calcitic). The geographic, climatic and oceanographic settings of the Ryukyu Islands provide an ideal natural laboratory to address each of these research questions.

Molecular Cloning of Silicatein Gene from Marine Sponge Petrosia ficiformis (Porifera, Demospongiae) and Development of Primmorphs as a Model for Biosilicification Studies - Marina Pozzolini; Laura Sturla; Carlo Cerrano; Giorgio Bavestrello; Laura Camardella; Anna Maria Parodi; Federica Raheli; Umberto Benatti; Werner E.G. Müller; Marco Giovine (Marine Biotechnology, 2004)

Conversion of carbonaceous material to graphite within the Greywacke Zone of the Eastern Alps - Gerd Rantitsch; Werner Grogger; Christian Teichert; Fritz Ebner; Christian Hofer; Eva-Maria Maurer; Bernhard Schaffer; Michael Toth (International Journal of Earth Sciences, 2004)

Discrepancy between nitrate reduction rates in intact leaves and nitrate reductase activity in leaf extracts: What limits nitrate reduction in situ? - Werner M. Kaiser; Andrea Kandlbinder; Maria Stoimenova; Johanna Glaab (Planta, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Isolation and characterization of a bacterium possessing L-phenylalanine dehydrogenase activity - Werner Hummel; Norbert Weiss; Maria-Regina Kula (Archives of Microbiology, 1984)